A POSTCOLONIAL ANALYSIS OF KARL MAYâS NOVEL âWINNETOU Iâ - Haq, Mishbahul; Mahmudah, Faiqah (Reflective, 2013)
The Research is conducted to analyze the superiority vs inferiority in novel Winnetou I. In this novel, white people is assumed as superior and black people as the inferior, the opinion comes along the bad image of black people, such as; dangerous people, uncivilized and related with violence. Vice versa, white people is always related with civilized person and have a high dignity. It is called binary opposition. The writer chooses Orientalism (Postcolonial theory) which is led by Edward said. The theory analyzes about wrong perception toward black people (Indian). In fact, white people (Europhean people) was spreding the bad description about black people and judge themselves are higher than black people.Keyword: Binary Opposition, Postcolonial Theory, Orientalism